A new species of the genus Terpnacarus Grandjean (Acari: Terpnacaridae) from Egypt - Momen, F. M.; Sayed, A. A.; Nasr, A. K. (Zootaxa, 2004)
A new terpnacarid mite, Terpnacarus zaheri sp. n., is described and illustrated. The new species was found in debris under date-palm at Badr town in New Valley, Egypt.